STRUKTUR KOMUNITAS MAKROZOOBENTHOS DI PERAIRAN SUNGAI SUIR KANAN KECAMATAN TEBING TINGGI BARAT KABUPATEN KEPULAUAN MERANTI - Yuslim Fauziah; Elya Febrita; Sholahudin Alayubi (Biogenesis, 2011)
The purpose of this research is to know community makrozoobenthos structure territorial water of sungai Suir Kanan of Subdistrict (Kecamatan) Tebing Tinggi Barat Kabupaten Kepulauan Meranti at August 2010. This research use method survey with intake sampel conducted five station. Especial parameter measured is type composition, what overflows, variety and dominansi. While parameter of supporter perceived is elementary substrat, organic substance, distrubed, pH, dissolve oxygen and free carbondixide. Result of research found makrozoobenthos more than 9 type full scalely 125 individual. Proportion of biggest type of Potamopyrgus sp and Tubifex-tubifex ( 18,4%). What overflows range from 237,01 - 474,03 ind/m2. What overflows highest type are type Potamopyrgus sp and Buccinum sp equal to 118,51 ind/ m2 and what overflows type low is Dytiscus sp equal to 29,62 ind/ m2 with there is no type predominating ( C = 0,14 - 0,28). Variety categorized a medium range from ( H') = 1,3 - 1,72, this means that as a whole the individual swampy forest every medium species. Can be said that environment territorial water of sungai Suir Kanan start to experience of trouble.